Investigation of roasting and photo-oxidative stability of cold-pressed peanut oil: Lipid composition, quality characteristics, and antioxidant capacity - El Idrissi, Zineb Lakhlifi; Elouafy, Youssef; El Moudden, Hamza; El Guezzane, Chakir; Lorenzo, Jose Manuel; Lee, Learn-Han *; Bouyahya, Abdelhakim; Maggi, Filippo; Caprioli, Giovanni; Harhar, Hicham; Tabyaoui, Mohamed (Elsevier, 2023)
In this study, the effect of conventional roasting and the photo-oxidative stability of two cold-pressed peanut oil varieties (Virginia and Valencia) were investigated. Changes in the concentrations of the fatty acids (including trans isomers), minor components, nutritional quality, and antioxidant capacity were analyzed and compared. The evolution of the oxidation status was measured by peroxide value (PV), acid value (AV), p-anisidine value (p-AnV), UV-spectrophotometric indexes (E232 and E270), total oxidation value (TOTOX), and browning index (BI). Results showed a slight change in AV, while relevant primary and secondary lipid oxidation was detected, leading to an increase in PV, p-AnV, as well as E232 and E270 indexes during roasting and photo-oxidation. Furthermore, exposure to UV light resulted in a remarkable degradation of tocopherol (71.67–100%), while phytosterols were reduced by 0.16–6.68%. Roasting, on the other hand, resulted in a significant increase (p < 0.05) in the content of phytosterols, tocopherols, chlorophyll, and carotenoid as well as antioxidant activity in peanut oil. In addition, Maillard reaction products (estimated by BI) also increased with roasting; afterward, these compounds gradually declined with UV light exposure. As for the fatty acid profile and nutritional indicators, a noticeable difference was observed between unroasted and roasted peanut oils throughout photo-oxidation.